2014
DOI: 10.1136/amiajnl-2013-002615
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the information seeking strategies of residents, nurse practitioners, and physician assistants in critical care settings

Abstract: The differences in the information seeking strategies are potentially a result of the differences in clinical training, strategies of managing cognitive load, and the nature of the use of available health IT tools. Further research is needed to investigate the effects of these differences on clinical and process outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…For example, respondents from our survey demonstrated that ready access to a single source was preferred just slightly over a tool that provides multiple links to various sources. These findings suggest that an infobutton with options for varying degrees of resource density may be a way to personalize these tools to the different information-seeking strategies of the user [35]. For example, users who prefer only a single source may select an option where point-of-care links would take a user directly to the UpToDate article (or similar source based on user preference) on the topic rather than have to select from a myriad of sources provided them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, respondents from our survey demonstrated that ready access to a single source was preferred just slightly over a tool that provides multiple links to various sources. These findings suggest that an infobutton with options for varying degrees of resource density may be a way to personalize these tools to the different information-seeking strategies of the user [35]. For example, users who prefer only a single source may select an option where point-of-care links would take a user directly to the UpToDate article (or similar source based on user preference) on the topic rather than have to select from a myriad of sources provided them.…”
Section: Discussionmentioning
confidence: 99%
“…As we develop new methods of inquiry, we will also be faced with ancillary challenges, such as (1) whether it is ethical to blind patients or clinicians to the high probability of an adverse event that can be prevented with available resources, (2) how information resources could affect patient behaviors (eg, treatment adherence in outpatient settings), and (3) determining optimal information visualization strategies for different clinicians and patients (given that a one-size-fits-all approach is likely inadequate 34 ). Although nurses were the clinicians highlighted in this review, all healthcare providers will soon be faced with these challenges pertinent to HPA, and healthcare is ready to have these issues explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other external constraints that play into the decisions regarding the priority order of patient presentation that can accelerate the disposition of patients in a unit. Tools supporting such global strategies and assisting in patient prioritization have been described to improve efficiency in critical care settings [38]. In an another study, Iapichino et al [39], suggested stratification of patients in intensive care settings should be based on their illness severity at patient admission to achieve cost effectiveness in the care delivery process.…”
Section: Discussionmentioning
confidence: 99%